ChemInform Abstract: Copper‐Catalyzed C(sp2)—H Amidation of Unactivated Arenes by N‐Tosyloxycarbamates. Issue 13 (1st April 2014) - John, Alex; Byun, Jeena; Nicholas, Kenneth M.
Abstract Optimal reaction conditions are elaborated for the amidation of benzene with N‐tosyloxycarbamate (I).